Discrimination of the binding mode of DNA ligands by single-photon timing. Issue 1 (2009) - Nardo Nardo, Luca Luca; Bondani Bondani, Maria Maria; Andreoni Andreoni, Alessandra Alessandra
Abstract : We perform time-correlated single-photon counting measurements with 30-ps resolution of the fluorescence emitted by the donor fluorophores of donor–acceptor pairs covalently labeling DNA synthetic oligonucleotides by using a non-commercial single-photon avalanche diode. The measurements allow us to precisely assess the fluorescence resonant energy transfer efficiency of the pairs in solutions containing the oligonucleotides and DNA–ligands, for different ratios of the DNA base-pair to ligand concentrations. A quantitative evaluation of the deformations of DNA double strands following the ligand binding is obtained, as the transfer efficiency is a steep function of the donor-to-acceptor distance. The results lead to an easy and cheap method to discriminate between the binding modes of minor groove and base intercalating ligands.